AC-Bipolar Electropolymerization of 3,4-Ethylenedioxythiophene in Ionic Liquids - Chen, Zhenghao; Zhou, Yaqian; Villani, Elena; Shida, Naoki; Tomita, Ikuyoshi; Inagi, Shinsuke (Langmuir, 2023)
Recently, alternating current (AC)-bipolar electropolymerization of 3,4-ethylenedioxythiophene (EDOT) has been reported to produce poly(3,4-ethylenedioxythiophene) (PEDOT) fibers from the terminals of bipolar electrodes in acetonitrile solution (MeCN) containing low concentrations of supporting salts in a template-free manner. Here, we extend such methodology in ionic liquid (IL) media. Three kinds of ILs, diethylmethyl(2-methoxyethyl)ammonium tetrafluoroborate ([DEME][BF4]), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]), and diethylmethyl(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide ([DEME][TFSI]), with different electric field transmission efficiencies and diffusion coefficients were employed as solvents for the AC-bipolar electropolymerization of EDOT. A variety of PEDOT morphologies were obtained in these three ILs, showing a relationship with the physicochemical properties of the ILs. We successfully confirmed the growth of PEDOT fibers in ILs and systematically discussed the factors that influenced their growth.